Bioactive secondary metabolites from marine and terrestrial microorganisms with expected antitumor activity - Mohamed Mamdouh Sayed Nagia; Atef Gobran Hanna; Soheir Mohamed Elzalabani (Cairo : Mohamed Mamdouh Sayed Nagia, 2012)
Natural products have always been the most successful source of drug leads . They maintain to supply greater structural diversity than standard combinatorial chemistry and thus propose major opportunities for finding new and novel low molecular weight leading structure that are biologically active against a wide range of assay targets
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacology
Issued also as CD
Keywords: Antitumor activity; Bioactive secondary metabolites; Terrestrial microorganisms